An Overview of Antimicrobial Activity of Lysozyme and Its Functionality in Cheese - Khorshidian, Nasim; Khanniri, Elham; Koushki, Mohammad Reza; Sohrabvandi, Sara; Yousefi, Mojtaba (Frontiers in Nutrition, 2022)
Due to the concern of consumers about the presence of synthetic preservatives, researchers and food manufacturers have recently conducted extensive research on the limited use of these preservatives as well as the introduction and use of natural preservatives such as herbal extracts and essential oils, bacteriocins and antimicrobial enzymes. Lysozyme is a natural enzyme with antimicrobial activity that has attracted considerable attention to be potentially utilized in various industries. Since lysozyme is an intrinsic component of the human immune system and has low toxicity; it could be considered a natural antimicrobial agent for use in food and pharmaceutical industries. Lysozyme exerts antimicrobial activity against microorganisms, especially Gram-positive bacteria, by hydrolyzing 1,4-beta-linkages between N-acetylmuramic acid and N-acetylglucosamine in the cell wall. In addition, increased antimicrobial activity of lysozyme against Gram-negative bacteria could be achieved by modification of lysozyme through physical or chemical interactions. Lysozyme is presented as a natural preservative in mammalian milk and can be utilized as bio-preservative in dairy products such as cheese. Both bacteria and fungi can contaminate and spoil the cheese; especially the one is made traditionally by raw milk. Furthermore, uncontrolled and improper processes and post-pasteurization contamination can participate in cheese contamination. Therefore, besides common preservative strategies applied in cheese production, lysozyme could be utilized alone or in combination with other preservative strategies to improve the safety of cheese. Hence, this study aims to review lysozyme’s antimicrobial properties as natural antimicrobial enzyme and its functionality in cheese.